Are Grandparents a Good Substitute for Parents as the Primary Caregiver? The Impact of Grandparents on Children's Academic Performance - Sophie Xuefei Wang; Cynthia Bansak (Global Labor Organization (GLO), 2022)
This study examines the impacts of caregiving by grandparents on children's academic performance in China, using data from the China Family Panel Studies (CFPS 2010 and 2014). Applying pooled OLS, instrumental variables and fixed-effects models with panel data estimation techniques, we find evidence that grandparents appear to have an adverse effect on the test scores of their school-age grandchildren. We further examine the mechanisms of this negative effect. Our results suggest that the education of grandparents plays an important role on the success of grandchildren and that increased schooling of grandparents can mitigate the negative effects of non-parental caregivers; thus, there are potential positive intergenerational impacts as grandparents become more educated themselves. When examining additional channels depressing test scores, we find evidence of grandparents' tendency to overindulge single-child grandchildren and grandsons. Lastly, it also appears that the common parenting practices of grandparents are detrimental to childhood development.
Keywords: I25; J13; O53; 330; children; grandparents; instrument variable; academic performance; China